2022
DOI: 10.1101/2022.02.10.479867
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lyophilized mRNA-lipid nanoparticle vaccines with long-term stability and high antigenicity against SARS-CoV-2

Abstract: Advanced mRNA vaccines play vital roles against SARS-CoV-2. However, due to the poor stability, most current mRNA delivery platforms need to be stored at -20 °C or -70 °C. Here we present lyophilized thermostable mRNA loaded lipid nanoparticles, which could be stored at room temperature with long-term stability. We demonstrate the applicability of lyophilization techniques to different mRNA sequences and lipid components. Three lyophilized vaccines targeting wild-type, Delta and Omicron SARS-CoV-2 variant were… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Incorrect storage can lead to oxidation and hydrolysis of the RNA and may alter their function [ 65 ]. Lyophilization might be an alternative storage method as it may enable long-term stability at higher temperatures [ 66 , 67 ].…”
Section: Rna Vaccinesmentioning
confidence: 99%
“…Incorrect storage can lead to oxidation and hydrolysis of the RNA and may alter their function [ 65 ]. Lyophilization might be an alternative storage method as it may enable long-term stability at higher temperatures [ 66 , 67 ].…”
Section: Rna Vaccinesmentioning
confidence: 99%
“…During lyophilization, the removal of water takes place via sublimation at low temperature under vacuum. Generally, lyophilization is comparatively a mild drying method and believed to enhance the stability issues mostly related to colloidal nanoparticles (NPs) and/or macro-biomolecules [145,146].…”
Section: Storage Issue Related To Mrna Vaccinesmentioning
confidence: 99%
“…Ai et al. recently studied the physical LNP characteristics, encapsulation efficiency, and size of lyophilized mRNA-LNPs at different temperatures and time points, albeit only for 18 days ( 193 ). Lyophilized mRNA-LNPs stored at 4°C and 25°C were stable for at least 18 days, showing no changes in size, encapsulation, and RNA integrity, while those stored at 40°C displayed an increase in size, without loss of RNA integrity or encapsulation efficiency.…”
Section: Application Of Mrna Technologiesmentioning
confidence: 99%
“…In vivo results showed comparable luciferase expression and anti-SARS-CoV-2 IgG titers when compared to fresh mRNA-LNPs. In addition neutralization antibodies against different SARS-CoV-2 variants were established and transgenic mice were protected in an infection-based model ( 193 ). An in-depth investigation into lyophilization of mRNA-LNPs recently revealed that storage at 4°C and below allowed maintenance of LNP size, polydispersity index and encapsulation efficiency for 24 weeks ( 182 ).…”
Section: Application Of Mrna Technologiesmentioning
confidence: 99%